Secure Data Transmission by Using Video Steganography - Mustafa, Mohd Fikri; Beh, Delina Mei Yin (Journal of Computing Technologies and Creative Content, 2019)
It is very essential to transmit important data like banking and military information in a secure manner. Video Steganography is the process of hiding some secret information inside a video. The addition of this information to the video is not recognizable by the human eye as the change of a pixel color is negligible. With the development of the technology, people have tend to figure out methods which are not only capable in hiding a message, but also capable of hiding the existence of a message. Steganography was introduced as a result of such research work. The proposed technique applies combination of insertion of metadata and blowfish encryption to embed the information into mp4 video files. The proposed method will hide secret information at random path of video metadata. The secret message will be encrypted using blowfish before hiding it into video metadata. When steganographed by this method, the probability of finding the hidden information by an attacker is lesser when compared to the normal method of hiding information frame-by-frame in a sequential manner. It also reduces the computational time taken for the extraction process and can hide huge amount of payload without effecting the steganography criteria.